Arterial revascularization in primary coronary artery bypass grafting: Direct comparison of 4 strategies—Results of the Stand-in-Y Mammary Study - Nasso, Giuseppe; Coppola, Roberto; Bonifazi, Raffaele; Piancone, Felice; Bozzetti, Giuseppe; Speziale, Giuseppe (The Journal of thoracic and cardiovascular surgery, 2009)
It is unclear (1) whether the use of 2 arterial conduits rather than a single conduit in multivessel coronary artery bypass grafting significantly improves results despite the concomitant use of saphenous vein grafts and (2) whether any among different configurations of composite grafts (left/right thoracic arteries and radial artery) offers an advantage over the others. Eight hundred fifteen patients were randomized to one of 3 different strategies of revascularization by using the left thoracic artery plus the right thoracic artery or using the left thoracic artery plus the radial artery. Venous grafts were used for the remaining targets. Patients randomized to receive 1 arterial graft served as control subjects. Operative mortality and morbidity were comparable among groups. The rate of cerebrovascular complications was not statistically lower among patients receiving 2 arterial grafts. At 2 years, overall survival was not significantly different among groups ( P = .59). Cardiac event–free survival was significantly better in patients receiving 2 arterial grafts versus control subjects ( P < .0001), even among elderly patients ( P = .022). The 3 investigated strategies using 2 arterial conduits were similar concerning early and midterm results. Revascularization with 2 arterial conduits offers better midterm event-free survival than a single arterial graft, irrespective of which second-choice arterial conduit is used (radial artery or right thoracic artery), the simultaneous use of saphenous vein grafts, and the patient's age.